Survey of Afghan (Dari) Language NLP for Building Afghan NLIDB System - Karimi, Sadullah (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2022.